Analisis Kelayakan Produksi Silikon dari Abu Ampas Tebu - Bambang Mulyana Hermanto; Erliza Noor; Yandra Arkeman; Etty Riani (Graduate School Bogor Agricultural University (SPs IPB), 2019)
It is estimated that the increase of sugarcane production will also increase the amount of bagasse. Sugar mills utilize dried bagasse as boiler fuel and the burning results a bagasse ash.Unrefined bagasse is estimated to contribute to the impact of the environment, including health problems when inhaled by humans. When covers the leaves, it will block the process of photosynthesis in plant. This are due to the size of ash and the contents of silica dioxide compound inside the bagasse. Besides providing impact, silica dioxide compounds are compounds that have high economic value as it can be used as silicon. The purposes of the utilization of bagasse ashes into silicon are to reduce the impact on the environment, to increase the economic value of bagasse ash and to empower community. The results of the feasibility analysis of silicon production from bagasse ash arethe planned production capacity of 10,000 tons/year, breakeven point (BEP) that is 3,400 tons/year or 34% of production capacity, Return of Investment (ROI) that is 28%, Payout Time (POT) of 3,6 years and 28,25% of Internal Rate of Return (IRR).Therefore, the plan to utilize the bagasse ash from silicon can be considered to be done.